2013
DOI: 10.1109/tpami.2012.247
|View full text |Cite
|
Sign up to set email alerts
|

3D Facial Landmark Detection under Large Yaw and Expression Variations

Abstract: Abstract-A 3D landmark detection method for 3D facial scans is presented and thoroughly evaluated. The main contribution of the presented method is the automatic and pose-invariant detection of landmarks on 3D facial scans under large yaw variations (that often result in missing facial data), and its robustness against large facial expressions. Three-dimensional information is exploited by using 3D local shape descriptors to extract candidate landmark points. The shape descriptors include the shape index, a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(80 citation statements)
references
References 26 publications
0
66
2
1
Order By: Relevance
“…Similarly, our method requires accurate and automatic landmark detection. For faces, [10] have shown that this is indeed achievable for 3D data. Finally, capture of a neutral face, while a manual process, is a trivial procedure performed only once per subject.…”
Section: Resultsmentioning
confidence: 90%
“…Similarly, our method requires accurate and automatic landmark detection. For faces, [10] have shown that this is indeed achievable for 3D data. Finally, capture of a neutral face, while a manual process, is a trivial procedure performed only once per subject.…”
Section: Resultsmentioning
confidence: 90%
“…Perakis et al [11], proposes a 3D landmark detection method for 3D facial scans. It based on Facial Landmark detector Model.…”
Section: Related Work:-mentioning
confidence: 99%
“…However, the PDM is sensitive to variations in expression and to incomplete coverage of the 3D face. Afterward, Perakis et al [10] introduced a 3D facial landmark localization method that was robust to yaw and expression changes. In [10], the shape index and spin image are used as features for detecting candidate landmarks e.g., eye corners, mouth corners, and nose tip.…”
Section: B Statistical Point Distribution Model-based Approachmentioning
confidence: 99%